2011
DOI: 10.1519/jsc.0b013e3181db9d4f
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Activation Patterns of the Upper and Lower Extremity During the Windmill Softball Pitch

Abstract: Fast-pitch softball has become an increasingly popular sport for female athletes. There has been little research examining the windmill softball pitch in the literature. The purpose of this study was to describe the muscle activation patterns of 3 upper extremity muscles (biceps, triceps, and rhomboids [scapular stabilizers]) and 2 lower extremity muscles (gluteus maximus and medius) during the 5 phases of the windmill softball pitch. Data describing muscle activation were collected on 7 postpubescent softball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 20 publications
3
34
0
Order By: Relevance
“…These MVC trials are similar to those often reported in the literature for these muscles (e.g. Potvin, 1997;Ervilha et al, 2005;Koyama et al, 2010;Oliver et al, 2011).…”
Section: Experimental Protocolsupporting
confidence: 88%
“…These MVC trials are similar to those often reported in the literature for these muscles (e.g. Potvin, 1997;Ervilha et al, 2005;Koyama et al, 2010;Oliver et al, 2011).…”
Section: Experimental Protocolsupporting
confidence: 88%
“…For example, Oliver et al (2011) investigated upper and lower extremity EMG during the softball pitch. Using MG and video concurrently, it was reported that there was consistent activation of lower extremity muscles throughout phases of the pitch.…”
Section: Discussionmentioning
confidence: 99%
“…The participant completed jump-throws from the 7-m penalty line using a standard men's handball after three running steps. A total of five successful attemps were recorded for each participant, with one minute rest between attemps; with the best attemp for each participant was selected for analysis [31,32].…”
Section: Protocolmentioning
confidence: 99%